Current practices in neonatal pain management: a decade after the last Italian survey - Paola Lago; Elisabetta Garetti; Patrizia Savant Levet; Immacolata Arenga; Anna Pirelli; Anna Chiara Frigo; Daniele Merazzi; on behalf Pain Study Group of Italian Society of Neonatology (Italian Journal of Pediatrics)
Abstract Background Neonates admitted to neonatal intensive care units (NICUs), as well as maternity nurseries, typically undergo painful invasive procedures during their hospital stay. We aim to report on current bedside analgesia/sedation and pain assessment practices, 10 years after the previous Italian survey. Methods This study employed a cross-sectional electronic survey. A 21-item questionnaire was distributed to directors of birth centers and NICUs to ascertain the policy for pain assessment and management in their respective units. A separate questionnaire was dispatched to neonatologists and nurses registered with the Italian Society of Neonatology. They reported on the analgesic strategies implemented for various painful bedside procedures. Both non-pharmacological and pharmacological analgesia interventions, as well as pain assessment, were analyzed. A regression model was utilized to identify factors that predict pain management practices. Results Data on pain management practices were collected from the directors of 153 NICUs and birth centers. Of these, 88.9% reported pain control following guidelines and 47.7% confirmed the presence of a local pain specialist promoting pain management in their unit. A minority, ranging from 16.3% to 41.8%, reported the use of a pain scale, a finding corroborated by the 200 doctors and 239 nurses who responded. At least one non pharmacological intervention (i.e., pacifier, sweet solution, or sensory saturation) was reported in 97.8% of the heel lances performed in the NICU and 96.5% in the maternity nursery, meanwhile for intramuscular injections in 73.8% and 70.3%, respectively. Additionally, it was reported that 22.9% of laryngoscopies were still performed without analgesia. Observations were made over 297 mechanical ventilation and 277 non-invasive ventilation courses, with non-pharmacological analgesia administered in 56.4% and 86.9% and the use of analgesic or sedative drugs in 81.7% and 17.1% of the cases, respectively. Furthermore, routine pain assessment was only undertaken in 68.0% and 64.9% of the cases. Conclusions We found a largely common propensity among Italian directors, neonatologists, and nurses to perform analgesic interventions for the most frequently encountered invasive neonatal painful procedures, though the practices are still highly variable. The availability of written guidelines and local pain specialists are confirmed as factors that contribute to the proper management of pain. However, pain assessment is still inadequate and urgently needs to be implemented to allow for tailored pain and stress control and prevention in all infants.